“It Used to Be That if It Weren’t Broken and Bleeding Profusely, I Would Never Go to the Doctor”: Men, Masculinity, and Health - Julie Gast PhD, CHES; Terry Peak MSW, PhD (American Journal of Men's Health, 2011)
Masculine gender scripts have been influential in health decision making in men. In addition, although past research has identified some success in using churches as sites for health education with women, little is known if similar programs would be successful with men. It is also unclear if religious beliefs influence the health attitudes and behaviors of men. Four focus groups with men from four religious denominations were conducted to learn about their health beliefs, attitudes, and behaviors, with the following themes emerging: men’s health fears, health promotion behaviors, spousal influence, aging and men’s health, and church-based health influence. Finally, the interaction of masculine gender scripts within these themes was considered.